Reimplantation Valve Sparing Procedure in Type A Aortic Dissection: A Predictive Factor of Mortality and Morbidity? - Farhat, Fadi; Bejan-Angoulvant, Theodora; Abdallah, Hassane; Jegaden, Olivier (IntechOpen, 2011)
None